Analisis Pemahaman Siswa tentang Salat Jamak dan Qashar: Perspektif Metode Pembelajaran dan Lingkungan Keluarga - Randi Saputra; Muhamad Fauzan; Hamzah Irfanda (Yayasan Literasi Altruis Khatulistiwa, 2025)
This study aims to analyze students’ understanding of salat jamak and qashar and to identify the factors that influence their ability to comprehend and practice these forms of worship. Conducted at SMP Negeri 1 Enam Lingkung, West Sumatra, this research employs a qualitative descriptive method with a phenomenological approach to explore students’ experiences, perceptions, and religious practices through interviews, observations, and questionnaires. The analysis focuses on students’ comprehension of the concepts, requirements, procedures, and contextual conditions for performing jamak–qashar, as well as the influence of teaching methods and family environment. The findings reveal that although most students are familiar with the basic concepts of jamak and qashar, only a small number are able to accurately explain the specific conditions under which these practices are permitted according to Islamic law. The variation in understanding is largely influenced by the effectiveness of the teaching methods used, with interactive and practice-based approaches proving more successful than traditional lecture methods. In addition, family involvement and students’ personal experiences during travel significantly contribute to strengthening their understanding of these worship practices. The study concludes that improving students’ understanding of jamak and qashar requires strong collaboration between schools, families, and the surrounding community. Enhancing learning strategies, providing real-life examples, and fostering a supportive religious environment are key factors in helping students comprehend and correctly apply the rules of jamak–qashar in accordance with Islamic teachings..